Cemas menghadapi dunia kerja? Antara konsep diri dan literasi media sosial pada mahasiswa - Ulfi Maulinda Hanum; Syaiful Fakhri (PSYCOMEDIA : Jurnal Psikologi, 2026)
Workplace anxiety is a phenomenon that occurs among students. The challenges faced in facing the world of work cause students to feel anxious when entering the world of work. This study aims to determine the relationship between self-concept and social media literacy with workplace anxiety in college students. This study uses a correlational quantitative method with a sampling technique in the form of convenience sampling. The subjects in this study were active final year undergraduate students at UIN Sunan Kalijaga, totaling 300 students. The research data collection used a world of work anxiety scale, self-concept scale, and social media literacy scale. Data analysis in this study used multiple linear regression analysis. The results of this study indicate that there is a relationship between self concept and social media literacy with workplace anxiety significantly with an effective contribution of 31.5%. The implication of this study shows that the importance of strengthening self concept and social media literacy skills in students in reducing the level of workplace anxiety.